Pharmacological targeting of smoothened receptor cysteine-rich domain by Budesonide promotes in vitro myelination - Recchia, Antonella Damiana; Dominicis, Alessandra; D'Amore, Vincenzo Maria; Fabiano, Tommaso; Al Jaf, Aland Ibrahim Ahmed; Peria, Simone; Basoli, Francesco; Rainer, Alberto; Marinelli, Luciana; Di Leva, Francesco Saverio; Ragnini-Wilson, Antonella (Frontiers in Molecular Neuroscience, 2024)
BackgroundThe myelin sheath ensures efficient nerve impulse transmission along the axons. Remyelination is a spontaneous process that restores axonal insulation, promoting neuroprotection and recovery after myelin damage. There is an urgent need for new pharmacological approaches to remyelination and to improve the most effective molecules. Some glucocorticoids (GC) were identified through phenotypical screens for their promyelinating properties. These GC compounds share the ability to bind the Smoothened (Smo) receptor of the Hedgehog (Hh) pathway. Gaining a deeper insight into how they modulate Smo receptor activity could guide structure-based studies to leverage the GCs’ potent promyelinating activity for a more targeted approach to remyelination.MethodsHere we focused on clarifying the mechanism of action of Budesonide, a GC known to bind the Smo cysteine-rich domain (CRD) and prevent Smo translocation to the cilium in fibroblasts. Our study employed a combination of cellular, biochemical and molecular dynamics approaches.ResultsWe show that treating oligodendroglial cells with Budesonide promotes myelination of synthetic axons and reduces Smo CRD conformational flexibility. This inhibits the Smo-mediated canonical signaling while activating the Liver Kinase B1 (LKB1)/ AMP-activated protein kinase (AMPK) pathway, leading to Myelin basic protein (MBP) expression.DiscussionThese insights pave the way for pharmacological targeting of Smo CRD to enhance oligodendrocyte precursor cells (OPCs) differentiation and improve remyelination.